Theological negotiations : proposals in soteriology and anthropology - Farrow, Douglas, 1953- (Grand Rapids.: : Baker Academic, 2018)
"One of today's leading theologians tackles some of the most significant themes in contemporary theology in light of the relationship between nature and grace"--
Theology and philosophy : recovering the Pax Thomistica -- Thinking with Aquinas about nature and grace -- Thinking with Luther about justification and sanctification -- Satisfaction and punishment : reckoning with Anselm -- Whose offering? Doxological Pelagianism as an ecumenical problem -- Transubstantiation : Sic transit mundus ad gloriam -- Autonomy : Sic transit anima ad infernum -- For the Jew first : reaffirming the Pax Paulinica -- The gift of fear : a meditation on Hebrews.
Includes bibliographical references and index.
Keywords: Theology, Doctrinal; Salvation -- Christianity; Theological anthropology